Lung Cancer Cells-Controlled Dkk-1 Production in Brain Metastatic Cascade Drive Microglia to Acquire a Pro-tumorigenic Phenotype - Gan, Dong-Xue; Wang, Yi-Bei; He, Ming-Yang; Chen, Zi-Yang; Qin, Xiao-Xue; Miao, Zi-Wei; Chen, Yu-Hua; Li, Bo (Frontiers in Cell and Developmental Biology, 2020)
Objectives Organotropism is primarily determined by tumor-derived exosomes. To date, the role of lung cancer cells-derived exosomes underlying the pre-metastatic niche formation is unclear. Materials and Methods The animal models of retro-orbital and intra-ventricular injection were constructed to administrate lung cancer cells-derived exosomes. Cytokine array was used to screen the cytokines released from brain endothelium after internalization of lung cancer cells-derived exosomes. The cellular co-culture system was established to mimic microglia-vascular niche contained lung cancer cells-derived exosomes. The levels of Dkk-1 and the activities of microglia were analyzed by qRT-PCR, western blot and immunofluorescence. In vivo selections of highly brain metastatic cells were performed to analyze the direct interaction of lung cancer cells with microglia. Results Animal studies demonstrated that there was a suppressive signal transferred from brain endothelium to microglia after internalization of lung cancer cells-derived exosomes into brain endothelium, which caused an absolutely less M1 phenotypic microglia and a relatively more M2 phenotypic microglia. Further results indicated that lung cancer cells-derived exosomes induced a release of endogenous Dkk-1 from brain endothelium, which rendered microglia to acquire a pro-tumorigenic feature in pre-metastatic niche. Subsequently, the declines of Dkk-1 in metastatic lung cancer cells removed the suppression on microglia and enhanced microglial activation in metastatic niche. Conclusion Our findings shed a new light on the synergistic reaction of the different cells in “neurovascular units” toward the metastatic messages from lung cancer cells and provided a potential therapeutic pathway for lung cancer metastasis to brain.